Dokładnośc badania postawy ciała metodą optoelektroniczną Diers Formetric III 4D w porównaniu z wynikiem zdjęcia RTG = Accuracy of the optoelectronic test body posture Formetric Diers Method III 4D in comparison with the result of the x-ray pictures - Paprocki, Michał Jerzy; Rychter, Paweł; Wilczyński, Jacek (Journal of Education, Health and Sport, 2016)
Paprocki Michał, Rychter Paweł, Wilczyński Jacek. Dokładnośc badania postawy ciała metodą optoelektroniczną Diers Formetric III 4D w porównaniu z wynikiem zdjęcia RTG = Accuracy of the optoelectronic test body posture Formetric Diers Method III 4D in comparison with the result of the x-ray pictures. Journal of Education, Health and Sport. 2016;6(4):385-398. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.50535 http://ojs.ukw.edu.pl/index.php/johs/article/view/3489 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.04.2016. Revised 25.04.2016. Accepted: 27.04.2016. DOKŁADNOŚC BADANIA POSTAWY CIAŁA METODĄ OPTOELEKTRONICZNĄ DIERS FORMETRIC III 4D W PORÓWNANIU Z WYNIKIEM ZDJĘCIA RTG Michał Paprocki, Paweł Rychter, Jacek Wilczyński Instytut fizjoterapii, Uniwersytet Jana Kochanowskiego w Kielcach, Polska mgr Michał Paprocki mgr Paweł Rychter dr hab. n o k.f. prof. UJK Jacek Wilczyński Streszczenie Wstęp: Celem przeprowadzonych badań była ocena dokładności badania postawy ciała metodą Diers Formetric III 4D w porównaniu z wynikami zdjęć RTG. Dokonano analizy zdjęcia RTG pacjenta oraz porównano go z wynikiem uzyskanym metodą Diers Formetric III 4D. Materiał i metody: Materiał badawczy stanowił jeden pacjent. Był nim chłopak w wieku lat 16 o wzroście 171cm i wadze 52,5 kg. Pacjent został poddany dwóm badaniom. Pierwsze to zdjęcie RTG całego kręgosłupa natomiast drugie badania zostało wykonane metodą Diers Formetric III 4D. Przed przystąpieniem do leczenia został zebrany wywiad pacjenta. Wyniki: Podsumowując wynik badania Diers Formetric III 4D można stwierdzić, że chłopiec ten miał skoliozę idiopatyczną trzyłukową. Metoda optoelektroniczna Diers formetric III 4D umożliwia szybki, pozbawiony szkodliwego promieniowania i wielkopowierzchniowy optyczny pomiar pleców i kręgosłupa. Porównując wyniki kątów skrzywienia oraz stopnia rotacji w obu badaniach można stwierdzić iż wyniki mieszczą się w błędzie pomiarowym. Słowa kluczowe: zdjęcie RTG, metoda Cobba, kąt skoliozy, postawa ciał. Abstract Introduction: The aim of the study was to assess the accuracy of the testing body posture Formetric Diers method III 4D in comparison with the results of X-RAY images. Analyses x-ray pictures of the patient and compares it with the result obtained by Formetric Diers III 4D. Material and methods: The research Material represented one patient. He is boy at the age of 16 years for growth 171cm and weight 52.5 kg. The patient was subjected to two tests. The first is a radiograph of the entire spine while the second test was done by Formetric Diers III 4D. Before attempting to treat the patient's interview has been harvested. Search results: summing up the result of the test Diers Formetric III 4Dd, it can be concluded that the boy had this three arcs idiopathic scoliosis. Optoelectronic method Diers Formetric III 4D provides fast, devoid of harmful radiation and measuring the optical centres of the back and spine. By comparing the results of the curvature of the angles and the degree of rotation in both studies, it can be concluded that the results are in the measuring error wrong. Keywords: x-ray, Cobb method, the angle of the scoliosis, attitude.